Prevalence of cervical HPV infection in women with systemic lupus erythematosus: A systematic review and meta-analysis (2019)
Objective: The objectives of this systematic review and meta-regression were: 1) to compare the prevalence of cervical HPV infection between SLE patients and healthy controls and 2) to evaluate the relationship between cervical HPV infection and traditional and SLE-related risk factors for cervical HPV infection in these patients. Methods: We conducted a systematic literature review (PubMed, Cochrane Library, Embase, Virtual Health Library and SciELO databases) following PRISMA guidelines and using meta-regression to investigate the pooled prevalence of cervical HPV infection in adult women with SLE. The articles included were independently evaluated by two investigators who extracted information on study characteristics, defined outcomes, risk of bias and summarized strength of evidence [Quality of evidence using the Oxford Centre for evidence-based medicine (EBM) Levels of Evidence]. Using meta-regression, we further analyzed whether factors such as multiple sexual partners and immunosuppressive therapy were associated with HPV prevalence. We evaluated the quality of evidence included using the Oxford Centre for EBM levels of evidence. Pooled odds ratios (ORs) and 95% confidence intervals (CI) were calculated for studies providing data on HPV prevalence in women with SLE and in healthy controls. Results: A total of 687 articles were identified; 9 full-text articles examining the prevalence of cervical HPV infection in SLE women were included, comprising 751 SLE women. Eight studies employed PCR using general primers. The HPV prevalence varied from 3.1% to 80.7%. In the random effects meta-analysis, the pooled prevalence of cervical HPV infection in SLE vs. controls was 34.15% (95% CI: 19.6%–52.5%) vs. 15.3% (95% CI 0.79–27.8%), OR = 2.87 (95% CI: 2.20–3.76) p and lt;.0001, with large between-study heterogeneity (I2 = 95.4%). When only SLE women were evaluated, meta-regression showed no significant differences between patients with and without a background of multiple sexual partners and any immunosuppressive therapy. In addition, the prevalence of cervical HPV infection did not significantly differ between SLE patients on azathioprine or cyclophosphamide. Conclusions: This meta-analysis suggests that the prevalence of cervical HPV infection is higher in SLE women than in healthy controls. However, multiple sexual partners and any immunosuppressive therapy or specific immunosuppressive treatment (azathioprine and cyclophosphamide) were not associated with the prevalence of cervical HPV infection. © 2018 Elsevier B.V.